PENGARUH PEMBERIAN AROMA TERAPI LAVENDER TERHADAP PENINGKATAN KUALITAS TIDUR PADA PENDERITA KANKER SERVIKS : EVIDENCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background:.Cervical cancer is still the cancer with the most sufferers in Indonesia. The long and tiring series of treatments for cervical cancer sufferers will cause other complaints. One of them is disturbed sleep patterns, due to fatigue or anxiety. Sleep is a necessity that humans need to give time to the organs of the body to rest and so that they can maintain the balance of the body's metabolism. Purpose: This study was to improve sleep quality for cervical cancer patients. Method: The method is searching journals on E-Data based publications were limited to 5 years, namely in the range 2017 to 2022. Results: Obtained A PSQI score of 6 was obtained before the intervention, then the patient was given lavender aromatherapy intervention every night before going to bed for 3 days. Then the results obtained PSQI score 4.Conclusion: Lavender aromatherapy can improve sleep quality due to the content of linalool and linaloyl acetate which have a sedative effect.